Medium density particleboard reinforced with bamboo laminas - Barbosa, Juliana C. [UNESP]; Michelon, Anderson L.S.; De Araujo, Victor A.; Gava, Maristela [UNESP]; Morales, Elen A.M. [UNESP]; Garcia, José N.; Lahr, Francisco A.R.; Christoforo, André L. (My University, 2015)
The objective of this work was to evaluate the effect of the addition of bamboo laminas of the species Dendrocalamus giganteus to three-layer medium density particleboard (MDP). These laminas were glued onto both the top and the bottom of each panel. With the manufactured panels laminated with bamboo, mechanical tests based on the Brazilian Standard ABNT NBR 14810 were carried out to determine the modulus of rupture (MOR) in static bending and the tensile strength parallel-to-surface. These mechanical tests were realized in particleboards of eucalyptus and in reinforced particleboard, both produced in the laboratory. The modulus of rupture and tensile strength parallel-to-surface of the laminated MDP had values close to those that have been reported. The reinforcements increased the values of these studied properties. Nevertheless, this fact indicated the possibility to produce a stronger MDP using bamboo lamina as surface layers. These results show the possibility of using coated-bamboo MDP for utilization in large spans, for example, in flooring for mezzanines with finish on both sides, and for robust furniture as bookshelves, beds, tables, etc.
Keywords: Bamboo; Lignocellulosic composites; Medium density particleboard; Reinforced panels; Wood